Green-Synthesis Nanopartikel SnO2 Termediasi Ekstrak Daun Pelawan (Tristaniopsis merguensis Griff.) - Mustari Mustari; Evi J; Aliefia Noor; Rifqi Almusawi Rafsanjani; Yuant Tiandho (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
SnO2 nanoparticles are materials that have great potential in gas sensor devices. In this article, the synthesis of SnO2 nanoparticles is carried out through the mediation of pelawan (Tristaniopsis merguensis Griff.) leaf extract. The use of mediators of natural materials in this synthesis aims to make the synthesis process more environmentally friendly and lower in cost compared to conventional chemical and physical methods. Pelawan extract contains high antioxidant compounds. Thus, it can inhibit the agglomeration of SnO2 particles. Based on the variation of pH synthesis, it is known that the highest purity of SnO2 phase occurs at pH 7 while for alkaline conditions, there is an impurity, i.e., Sn6O4(OH)4. Calcination temperature has a very significant effect on the growth of SnO2 nanoparticle crystals. High temperatures will increase the size of the crystallite and the crystallinity. Keywords: green-synthesis, pelawan, tin oxide